Joining and cycling performance of ultra-thick tungsten coatings on patterned steel substrates for fusion armour applications - Cui, W; Flinders, K; Hancock, D; Grant, PS; Grant, PS (Elsevier, 2021)
Tungsten is the leading candidate to provide a critical protective coating for copper and steel-based plasma facing components in nuclear reactors. However, fabrication of thick tungsten coatings on copper or steel is challenged by the significant difference in the melting points and the thermal expansion coefficients of the materials, which leads to severe thermal expansion mismatch strains during manufacture and in service. This challenge is investigated using a new processing approach — field assisted sintering of tungsten nanopowders directly onto pre-sculptured steel component surfaces to induce controlled, vertical segmentation cracks that provide strain relief. Tungsten coatings up to 2 mm thick were fabricated with uniform density and with a microstructure consisting of ultrafine grains of ∼200 nm. The coatings showed outstanding thermal cycling durability and survived for at least 50 cycles under pulsed temperature cycles between 300 to 800 °C. Microscopy and in situ thermal imaging revealed that a previously unachievable thermal expansion mismatch strain tolerance was provided by a combination of enhanced tungsten coating adhesion and deliberate coating segmentation by vertical cracking. The approach should be readily adaptable to other dissimilar materials systems to facilitate a range of durable, ultra-thick low ductility coatings on metallic substrates.